Altered Protein Abundance and Localization Inferred from Sites of Alternative Modification by Ubiquitin and SUMO. Issue 21 (15th October 2021) - Ulman, Adi; Levin, Tal; Dassa, Bareket; Javitt, Aaron; Kacen, Assaf; Shmueli, Merav D.; Eisenberg-Lerner, Avital; Sheban, Daoud; Fishllevich, Simon; Levy, Emmanuel D.; Merbl, Yifat
Graphical abstract: Highlights: Sites of Alternative Modifications (SAMs) are more abundant than previously appreciated. SUMO-ubiquitin SAMs are revealed in more than 4000 proteins across the proteome. Ubiquitin-SUMO SAM proteins have increased protein abundance and altered cyto-nuclei localization. SAM-associated features are functionally conserved from yeast to human. Abstract: Protein modification by ubiquitin or SUMO can alter the function, stability or activity of target proteins. Previous studies have identified thousands of substrates that were modified by ubiquitin or SUMO on the same lysine residue. However, it remains unclear whether such overlap could result from a mere higher solvent accessibility, whether proteins containing those sites are associated with specific functional traits, and whether selectively perturbing their modification by ubiquitin or SUMO could result in different phenotypic outcomes. Here, we mapped reported lysine modification sites across the human proteome and found an enrichment of sites reported to be modified by both ubiquitin and SUMO. Our analysis uncovered thousands of proteins containing such sites, which we term Sites of Alternative Modification (SAMs). Among more than 36, 000 sites reported to be modified by SUMO, 51.8% have also been reported to be modified by ubiquitin. SAM-containing proteins are associated with diverse biological functions including cell cycle, DNA damage, and transcriptional regulation. As such, our analysis highlights numerous proteins and pathways as putative targets for further elucidating the crosstalk between ubiquitin and SUMO. Comparing the biological and biochemical properties of SAMs versus other non-overlapping modification sites revealed that these sites were associated with altered cellular localization or abundance of their host proteins. Lastly, using S. cerevisiae as model, we show that mutating the SAM motif in a protein can influence its ubiquitination as well as its localization and abundance.